Self-sustained combustion of CO with transient changes and reaction mechanism over CuCe0.75Zr0.25Oδ powder for honeycomb ceramic catalyst. (1st March 2020) - Kang, Running; Wei, Xiaolin; Ma, Pandong; Bin, Feng; He, Junyao; Hao, Qinglan; Dou, Baojuan
Graphical abstract: Highlights: The powder sample is well designed and coated on the HC tube to form CuCe0.75 Zr0.25 Oδ /HC catalyst. The transient changes and two-dimensional temperature region are obtained for CO self-combustion via CO-TPO + FLIR. The various intermediate species and competitive adsorption of reactants on different active sites are evidenced. The different pathways and roles of M-K and L-H mechanisms are proposed using in situ IR. Abstract: A CuCe0.75 Zr0.25 Oδ catalyst was prepared by the sol-gel method and successfully coated on honeycomb ceramic (HC) carrier. The activity of CuCe0.75 Zr0.25 Oδ /HC was determined by the CO-TPO + FLIR, with the results performing that the critical condition for CO self-sustained combustion is 3 vol% CO + 3 vol% O2 /N2 at 0.5 L/min. As the CO concentration increases from 1 vol% CO to 3 vol% CO, the induction process (15 ) shifts toward a slower CO conversion, while the light-off process (>T15 ) shifts to rapid ignition with a transient change for the CO oxidation reaction. The furnace temperature for CO self-sustained combustion decreases with increasing the CO and O2 concentrations. Upon increasing the CO2 concentration, however, furnace temperature is needed to increase and realize CO complete conversion. The thermal stability test combined with SEM + EDX results indicate that the CuCe0.75 Zr0.25 Oδ /HC retains an excellent thermal stability after a 200 h, and the high-temperature region remains at 225 ± 1 °C during the CO self-combustion reaction. The activity of catalyst is reduced slightly after the 200 h test because of the carbon deposition on the catalyst surface, but such a slight deactivation can be eliminated by the air oxidation method. In situ IR results show a competitive adsorption of CO/O2 and CO2 on the Cu-Ce active sites, indicating that the addition of gaseous CO2 performs an inhibition of CO oxidation. CO preferentially adsorbs linearly at Cu + sites to form carbonyls that react with lattice oxygen to produce CO2 to release, which can be ascribed to M-K mechanism. The L-H mechanism is less important, which involves the relatively weak reaction of adsorbed CO and adsorbed oxygen on the Cu-Ce active sites to form carbonate species.